Implementation of Regulation of The Minister of Religion Number 2 of 2012 for Islamic Education Supervisers at Schools in The Department of Education in Sukabumi Regency - Ia Hidarya; Achmad Mudrikah; R. Supyan Sauri (International Journal of Nusantara Islam, 2020)
Regulation of the Minister of Religion (PMA) Number 2 of 2012 concerning Madrasah Supervisors and Supervisory Islamic Religious Education (PAI) at Schools, is a policy product issued by the Ministry of Religion which gave rise to a new nomenclature, amidst the regulations of School / Madrasah supervisors, namely supervisory functional positions. PAI on Schools. This regulation has implications for the implementation of PAI supervisor duties at schools. This research was motivated by the inadequate implementation of the activities of Islamic Education Supervisors at schools in the Sukabumi District Education Office. The focus of this research is the implementation of Regulation of the Minister of Religion (PMA) Number 2 of 2012 for Islamic Education supervisors at schools in the Sukabumi District Education Office. The purpose of this research is to find out about: 1) Implementation of PMA Number 2 of 2012 for PAI supervisors in the Education Office of Sukabumi Regency; 2) Problems faced by PAI supervisors at the Education Office of Sukabumi Regency in implementing PMA Number 2 of 2012, and 3) Efforts to improve in the future in implementing PMA Number 2 of 2012. This study used a qualitative approach with descriptive methods, data collection was carried out through interviews, observation and documentation study. This is to make a systematic, factual and accurate description of the phenomenon under study. The results of the research findings show: 1) The implementation of PMA Number 2 of 2012 for PAI supervisors at the Education Office of Sukabumi Regency is not running optimally; 2) The root of the main problems faced by PAI supervisors: Policy standards; Budget; Psychological burden; Coordination; and performance appraisal. 3) Improvement efforts are made by: Directorate of PAI by compiling a draft revision of PMA Number 2 of 2012; The Sukabumi District Education Office issues a SK to assign a school supervisor to the PAI supervisor; The Ministry of Religion of Sukabumi Regency has substantially increased the pattern of guidance; PAI supervisors increase creativity and motivation in carrying out their duties and supervisory functions. Recommendations for this study are addressed to the PAI Directorate of the Ministry of Religion of the Republic of Indonesia, in the form of: PMA Revision Number 2 of 2012 so that it is relevant to the regulations of school / madrasah supervisors; Review of Islamic Religious Education (PAI) supervisor nominations in schools; Adequacy of the budget for improving the quality of supervisors; and Strengthen coordination between related institutions.